Programa DEAG para mejoramiento de la comprensión de textos expositivos en estudiantes de quinto grado de educación secundaria de la Institución Educativa Teniente Manuel Clavero Muga, Iquitos 2022 - Arimborgo Guerra, Debbie Elizabeth (2025)
The objective of the study was to evaluate the effect of the DEAG program on improving the understanding of expository texts in fifth grade secondary school students at the Teniente Manuel Clavero Muga Educational Institution, in Iquitos. The population was divided into two groups, of which 30 made up the experimental group and 31 the control group. As an instrument, a questionnaire with expository texts was used to measure the level of reading comprehension in three dimensions: literal, inferential and critical comprehension. The results through the inferential analysis with the T-Student test showed that the DEAG program had a positive impact on literal and inferential comprehension, with statistically significant differences between the experimental group and the control group (p<0.01 and p=0.002 respectively). However, no significant differences were found in critical understanding (p=0.575). It was concluded that the DEAG program significantly improved the comprehension of expository texts, mainly in the literal and inferential dimensions. However, for critical understanding, it is recommended to complement the intervention with specific analysis and argumentation strategies.